Effect of Adding of Bacteriocin Produced from Streptococcus thermophilus Bacteria on the Microbial Content and Some Pathogenic Bacteria in Soft Cheese (NTU Journal of Agriculture and Veterinary Science, 2024)
This study was conducted at the College of Agriculture at Tikrit University for the period from the beginning of May until the end of September 2022. The effect of adding bacteriocin produced from Streptococcus thermophilus bacteria in the manufacture of soft cheese was studied. The cheese was made from pasteurized cow's milk with the addition of (0.5%, 1%, 1.5%, 2% of bacteriocins) and its microbial content (aerobic bacteria, coliform bacteria, yeasts and molds) was studied during the refrigerated storage period (at 5 ± 1 °C). For 28 days. And a study of the effect of bacteriocins on (Staphylococcus aureus, Bacillus cereus, Escherichia coli) as pathogenic bacteria in soft cheese. The results of the statistical analysis of these factors showed that there were significant differences in the total numbers of microorganisms in the soft cheese produced. The addition of bacteriocin had a clear effect on all types of microorganisms under study during the storage period.